Postoperative Acute Kidney Injury by Age and Sex: A Retrospective Cohort Association Study. (10th November 2022) - Privratsky, Jamie R.; Fuller, Matthew; Raghunathan, Karthik; Ohnuma, Tetsu; Bartz, Raquel R.; Schroeder, Rebecca; Price, Thomas M.; Martinez, Michael R.; Sigurdsson, Martin I.; Mathis, Michael R.; Naik, Bhiken; Krishnamoorthy, Vijay
Abstract : Background: Acute kidney injury (AKI) after noncardiac surgery is common and has substantial health impact. Preclinical and clinical studies examining the influence of sex on AKI have yielded conflicting results, although they typically do not account for age-related changes. The objective of the study was to determine the association of age and sex groups on postoperative AKI. The authors hypothesized that younger females would display lower risk of postoperative AKI than males of similar age, and the protection would be lost in older females. Methods: This was a multicenter retrospective cohort study across 46 institutions between 2013 and 2019. Participants included adult inpatients without pre-existing end-stage kidney disease undergoing index major noncardiac, nonkidney/urologic surgeries. The authors' primary exposure was age and sex groups defined as females 50 yr or younger, females older than 50 yr, males 50 yr or younger, and males older than 50 yr. The authors' primary outcome was development of AKI by Kidney Disease-Improving Global Outcomes serum creatinine criteria. Exploratory analyses included associations of ascending age groups and hormone replacement therapy home medications with postoperative AKI. Results: Among 390, 382 patients, 25, 809 (6.6%) developed postoperative AKI (females 50 yr or younger: 2, 190 of 58, 585 [3.7%]; females older than 50 yr: 9, 320 of 14, 4047 [6.5%]; males 50 yr or younger: 3, 289 of 55, 503 [5.9%]; males older than 50 yr: 11, 010 of 132, 447 [8.3%]). When adjusted for AKI risk factors, compared to females younger than 50 yr (odds ratio, 1), the odds of AKI were higher in females older than 50 yr (odds ratio, 1.51; 95% CI, 1.43 to 1.59), males younger than 50 yr (odds ratio, 1.90; 95% CI, 1.79 to 2.01), and males older than 50 yr (odds ratio, 2.06; 95% CI, 1.96 to 2.17). Conclusions: Younger females display a lower odds of postoperative AKI that gradually increases with age. These results suggest that age-related changes in women should be further studied as modifiers of postoperative AKI risk after noncardiac surgery. Abstract : In this large retrospective cohort analysis, younger females were at lower odds of postoperative acute kidney injury than females of older age and males of all ages.